Positive effects of the religious /spiritual practices in mourning - Yoffe, Laura (2012)
The Positive Psychology Approach is complementary to the Religion and Spiritual Psychology.The Positive Psychology Approach is complementary to the Religion and Spiritual Psychology.Both areas study how to cope, or promote faith and hope states, positives states tending topromote psychophysical, affective, mental as well as the spiritual health of the human being.Pargament (1997) and Koenig (1997/2007) emphasize that religious practices have a beneficialeffect to health as it diminishes or prevents stress. Therefore, religion is seen as a potentialsource of mental health.My Doctoral Thesis research carried out with religious subjects from different creeds found thatprayers, contemplation and spiritual healing help to promote positive states of psychophysical,mental and spiritual welfare of relatives. (Yoffe, 2006/2010)